Can executive control be influenced by performance feedback? Two experimental studies with younger and older adults - Drueke, Barbara; Boecker, Maren; Mainz, Verena; Gauggel, Siegfried; Mungard, Lydia (Frontiers in Human Neuroscience, 2012)
Executive control describes a wide range of cognitive processes which are critical for the goal-directed regulation of stimulus processing and action regulation. Previous studies have shown that executive control performance declines with age but yet, it is still not clear whether different internal and external factors - as performance feedback and age - influence these cognitive processes and how they might interact with each other. Therefore, we investigated feedback effects in the flanker task in young as well as in older adults in two experiments. Performance feedback significantly improved executive performance in younger adults at the expense of errors. In older adults, feedback also led to higher error rates, but had no significant effect on executive performance which might be due to stronger interference. Results indicate that executive functions can be positively influenced by performance feedback in younger adults, but not necessarily in older adults.